Pharmacogenomics of Cardiovascular Pharmacology: Pharmacogenomic Network of Cardiovascular Disease Models - Toshio Tanaka; Takehiko Oka; Yasuhito Shimada; Noriko Umemoto; Junya Kuroyanagi; Chikara Sakamoto; Liqing Zang; Zhipeng Wang; Yuhei Nishimura (Elsevier, 2008)
The most important strategies in pharmacogenomics are gene expression profiling and the network analysis of human disease models. We have previously discovered novel drug target candidates in cardiovascular diseases through investigations of these pharmacogenomics. The significant induction of S100C mRNA and protein expression was detected in the rat pulmonary hypertension and myocardial infarction model. We also found increased taurine in hypoxia, a calcium-associated cytoprotective compound, to suppress the hypoxia-induced S100C gene expression and vascular remodeling. These results suggest that S100C may be one of the potential novel drug targets in hypoxic or ischemic diseases. Delayed cerebral vasospasm after aneurysmal subarachnoid hemorrhage causes cerebral ischemia and infarction. Using a DNA microarray, a prominant upregulation of heme oxygenase-1 (HO-1) and heat shock protein (HSP) 72 mRNAs were observed in the basilar artery of a murine vasospasm model. Antisense HO-1 and HSP 72 oligodeoxynucleotide inhibited HO-1 and HSP 72 induction, respectively, and significantly aggravated cerebral vasospasm. Moreover, we have also developed a unique heart failure model in zebrafish and identified several candidate genes as novel drug targets. These results suggest that pharmacogenomic network analysis has the potential to bridge the gap between in vitro and in vivo studies and could define strategies for identifying novel drug targets in various cardiovascular diseases. Keywords:: pharmacogenomics, network analysis, transcriptome, DNA microarray, therapeutic gene